Giant centipede length 13", Trinidad - (:unkn) unknown (F.P Bruce Austin,Trinidad, 2011)
The postcard shows a giant centipede that has been mounted. Centipedes have an odd number of pairs of legs never even numbers.
Colour: Sepia; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Centipedes--Trinidad and Tobago